ChemInform Abstract: Structural Chemistry of Silicates: New Discoveries and Ideas. Issue 49 (17th November 2016) - Pushcharovsky, Dmitry Yu.; Zubkova, Natalia V.; Pekov, Igor V.
Abstract: Review: 59 refs.